Historic Fertility Patterns in a Northern Ontario Ojibwa Community: The Fort Hope Band - Herring, D. Ann; Driben, Paul; Sawchuk, Lawrence A. (Anthropologica, 2022)
This paper describes the fertility patterns of a cohort of Ojibwa women who were registered members of the Fort Hope Indian Band and who married in the late contact traditional period between 1930 and 1944. The study on which the paper is based is unusual in that data used for reconstructing the cohort’s reproductive patterns are derived almost exclusively from pre-1960 treaty annuity lists. It is suggested that Canadian government records of native populations may be more useful for studying historic demographic patterns than was previously supposed.